2020
DOI: 10.1038/s41598-020-58413-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype assessment via a large scale socio-demographic survey favours yearlong Standard time over Daylight Saving Time in central Europe

Abstract: Abandoning daylight saving time in europe raises the topical issue of proper setting of yearlong social time, which needs mapping of various socio-demographic factors, including chronotype, in specific geographic regions. This study represents the first detailed large scale chronotyping in the Czech Republic based on data collected in the complex panel socio-demographic survey in households (total 8760 respondents) and the socio-physiological survey, in which chronotyped participants also provided blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 66 publications
8
34
2
Order By: Relevance
“…In line with earlier research Sl adek et al, 2020), we found that respondents from lower longitudes with the same time zone had on average later chronotypes, a finding that generalizes across most individual time zones. These individuals experience sunset and sunrise times at a later clock time as a result of their more westward location within the time zone which entrains a later chronotype .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with earlier research Sl adek et al, 2020), we found that respondents from lower longitudes with the same time zone had on average later chronotypes, a finding that generalizes across most individual time zones. These individuals experience sunset and sunrise times at a later clock time as a result of their more westward location within the time zone which entrains a later chronotype .…”
Section: Discussionsupporting
confidence: 92%
“…Since our method of estimating the latter two phenotypes was novel and relied on non-targeted questionnaire responses instead of proper psychometric scales, one goal of our study was to demonstrate the validity of this approach by replicating robust findings about our phenotypes. We successfully replicated previous findings about the relationship between age, sex and chronotype (Duarte et al, 2014;Fischer et al, 2017;Paine et al, 2006;Till Roenneberg et al, 2004;Sl adek et al, 2020;Tonetti et al, 2008), relative longitude and chronotype (Giuntella & Mazzonna, 2019;Sl adek et al, 2020) as well as city population and both chronotype and cognitive ability (Abdellaoui et al, 2019;Alexopoulos, 1997;Bass et al, 2008;Gist & Clark, 1938;Lehmann, 1959;Sl adek et al, 2020;Taji et al, 2019;Teasdale et al, 1988). Notably, we also found a modest positive relationship between cognitive ability and chronotype (β = .05), in line with a previous meta-analysis (Preckel et al, 2011) and a large study (Kanazawa & Perina, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite extensive investigation of parental sleep patterns and quality during pregnancy and following childbirth as well as its relationship with mental health complications ( Deforges et al, 2021 ), only little is known about parental circadian rhythm during this time. Initial evidence suggests that parenthood is linked with an early chronotype ( Sládek et al, 2020 ). Further, parental circadian rhythm amplitude may be decreased following birth ( Wulff and Siegmund, 2000 ), which can be observed as a result of irregular sleep-wake patterns or disturbance and may accumulate to circadian rhythm sleep disorder ( Zee and Vitiello, 2009 ).…”
Section: Epidemiological Evidence Towards Circadian Regulation Of Men...mentioning
confidence: 99%